2012
DOI: 10.3892/or.2012.1768
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hepatoma-derived growth factor suppresses the malignant phenotype of U87 human glioma cells

Abstract: Abstract. Hepatoma-derived growth factor (HDGF) has been shown to correlate with increased malignancy of different types of tumors and could be an independent prognostic index for human cancers. We previously found that HDGF is overexpressed in glioma tissues and that its expression level may correlate with the clinical pathological grade. In the present study, we investigated the effects of HDGF downregulation on the biological behaviors of U87 glioma cells. Our results showed that HDGF knockdown significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As is well known, lentiviruses have the capacity to integrate into the genome of host cells; thus, they are extensively used as vectors for shRNA expression 28. Some studies showed that HDGF depletion significantly reduced cancer cell proliferation, migration and invasion, including in gallbladder cancer, gastric cancer, and human glioma cells,2931 but in contrast to the above results, Guo, Z., et al found that downregulation of HDGF stimulated cell migration and invasion in breast cancer 32. We first investigated the correlations between HDGF expression and BCa, and we found that HDGF deletion significantly inhibited the malignant phenotype of T24 and 253J cells, including proliferation, colony formation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, lentiviruses have the capacity to integrate into the genome of host cells; thus, they are extensively used as vectors for shRNA expression 28. Some studies showed that HDGF depletion significantly reduced cancer cell proliferation, migration and invasion, including in gallbladder cancer, gastric cancer, and human glioma cells,2931 but in contrast to the above results, Guo, Z., et al found that downregulation of HDGF stimulated cell migration and invasion in breast cancer 32. We first investigated the correlations between HDGF expression and BCa, and we found that HDGF deletion significantly inhibited the malignant phenotype of T24 and 253J cells, including proliferation, colony formation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ionizing radiation enhances esophageal epithelial cell migration and invasion through a paracrine mechanism involving stromal-derived HGF [20]. HGF contributed to the HDGF-associated aggressive behavior of cancer cells [32]. Our study also showed that irradiated fibroblasts promoted ESCC cells scattering abilities, which was a well-characterized behavior activated by HGF/c-Met system [16].…”
Section: Discussionmentioning
confidence: 77%
“…Signaling through receptor tyrosine kinases such as hepatocyte growth factor and epidermal growth factor receptor are known to drive the malignant behaviors of U87MG cells, at least in part, via downstream Akt signaling. 4,36,37 We previously showed that RNAi-mediated knockdown of ACSVL3 disrupted RTK-Akt signaling. 4 Lipid raftsplasma membrane microdomains that are enriched in sphingolipids and cholesterolare thought to be organizing centers or platforms for signaling receptors.…”
Section: Discussionmentioning
confidence: 99%